The Effect of Self-Regulated Learning on Procrastination Behavior of Fifth-Grade Students in Pancasila Education at SDN Gurah 1 - Dian Kusumawati (Indonesian Journal Publisher, 2026)
Procrastination behavior is exhibited by fifth-grade students in the Pancasila Education subject at SDN Gurah 1, as indicated by delays in submitting assignments and less optimal understanding of Pancasila values. Self-regulated learning trains students to manage time, set learning goals, and independently monitor and evaluate their learning processes. This study aims to: (1) analyze the level of students’ self-regulated learning; (2) identify the level of students’ procrastination behavior in Pancasila Education learning; and (3) examine the relationship and effect of self-regulated learning ability on students’ procrastination behavior. This research employed a quantitative approach using an ex post facto method. Data were collected through closed-ended questionnaires using a Likert scale to measure levels of self-regulated learning and procrastination behavior, complemented by documentation to obtain supporting data. The data collection instruments consisted of self-regulated learning and procrastination behavior questionnaires that had been tested for validity and reliability. Data analysis techniques included descriptive analysis to describe data characteristics, prerequisite tests (normality and linearity tests), and inferential analysis using simple regression to determine the effect of self-regulated learning on students’ procrastination behavior. The results of the simple regression analysis indicate that self-regulated learning has a negative and significant effect on students’ procrastination behavior. Based on these findings, teachers are encouraged to consistently integrate self-regulated learning strategies into the learning process to reduce procrastination behavior among fifth-grade students at SDN Gurah 1.